Sustainable and secure trajectories for the military Internet of Drones (IoD) through an efficient Medium Access Control (MAC) protocol. (March 2019) - Choudhary, Gaurav; Sharma, Vishal; You, Ilsun
Highlights: An efficient MAC model is proposed that supports effective timing generation and control over IoD. Sustainable and secure trajectories are generated by using deep neural networks. The proposed approach mitigates certain known attacks, such as coagulation attacks on UAVs. The proposed model dynamically computes the waypoints which eliminate any possibilities of collisions. Abstract: Internet of Drones (IoD) involves cooperation and policing amongst Unmanned Aerial Vehicles (UAVs) based on waypoints generated through a series of algorithms. The dynamic reconfigurability of conveyances in IoD demands a secure trajectory and channel accessibility which is procurable through an efficient Medium Access Control (MAC) protocol. The majority of existing works considers the security of UAV-trajectories as a part of cryptographic and channel accessibility only, whereas the proposed approach idealizes link stability as one of the essential components for attaining secure trajectories. Furthermore, this paper proposes a deep neural network-based security framework, which embeds an efficient MAC protocol controlled by Macaulay's duration. The proposed approach fortifies that an extensive control over links provides an adequate duration for enhancing the security aspects of IoD and launching countermeasures against any known cyber attacks.